A major practicum report at General Tuna Corporation, Tambler, General Santos City - Badilles, Kristine Campos
The plant practice was conducted at General Tuna Corporation, Tambler, General Santos City from April 17 to May 22, 2006. The trainee was given 288 hours to be exposed in different areas of the company. These areas include the Production Line of the export division in both canned and pouched tuna processing. Quality Control, Chemical Laboratory, Sensory Laboratory and Research and Development. The objective of the plant practice is to gain experience in the operations involved in tuna processing. Through plant practice, the trainee was exposed to the actual food industry and was able to integrate the theories and principles learned from the academe
Thesis (BS Food Technology) -- University of the Philippines Mindanao, 2006
Keywords: Tuna; Tuna -- Canning; Tuna -- Canning -- Process; Canned tuna; Pouched tuna; General Tuna Corporation; General Tuna Corporation -- Tambler,General Santos City